Pengaruh Pengungkapan Corporate Social Responsibility dan Good Corporate Governace Terhadap Nilai Perusahaan - Dewi Selviyanti; Jaurino Jaurino; Wilda Sari (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
This This study aims to see how the Effect of Corporate Social Responsibility, the mechanism of Good Corporate Governance on the Value of Mining Companies listed on the Indonesia Stock Exchange in 2017-2019. The independent variables used in this study are Corporate Social Responsibility, Managerial Ownership, Institutional Ownership, Independent Board of Commissioners, and Audit Committee. The research sample obtained in this study were 18 companies. Data analysis techniques used are descriptive statistics, classical assumption test and multiple linear regression analysis. The results of the study using multiple linear regression analysis show that Corporate Social Responsibility has a significant effect on Firm Value with a significance value of 0.046 greater than 0.05. Managerial Ownership has a positive and significant effect on Firm Value with a significance value of 0.000 less than 0.05. Institutional Ownership Composition has a significant effect on Firm Value with a significance value of 0.006 greater than 0.05. The Independent Board of Commissioners has a significant negative effect on company value with a significance value of 0.038 greater than 0.05. The Audit Committee has no significant effect on firm value with a significance value of 0.478 greater than 0.05.